AKULTURASI BUDAYA MINANGKABAU DAN MANDAILING DALAM PROSES PERNIKAHAN DI NAGARI UJUNG GADING PASAMAN BARAT (1983-2000) - Desi Erita Saputri (Adisam Publisher, 2025)
This research examines the cultural acculturation between Minangkabau and Mandailing in marriage processes in Nagari Ujung Gading, West Pasaman during the period of 1983-2000. Nagari Ujung Gading is a border area inhabited by two major ethnic groups, Minangkabau and Mandailing, each with different cultural characteristics. The focus of the research is on the acculturation process, the dominance of Minangkabau culture, and the position of Mandailing culture in the context of marriage. The research uses a qualitative approach with heuristic historical research methods. Primary data was obtained through interviews with traditional leaders and local communities, as well as written documents such as traditional tambo books. The results show that the acculturation process occurred through long-term social interactions that began with the migration of Mandailing people to the Pasaman region. Minangkabau culture dominates the wedding procession due to geographical, social, and cultural factors. Nevertheless, Mandailing culture maintains a significant position in several elements of marriage, especially in the tradition of dowry money (uang hantaran) and mangupa-upa ritual. This acculturation not only gave birth to unique marriage practices but also created a hybrid cultural identity reflected in language and traditional rituals.